Natural Plants Compounds as Modulators of Epithelial-to-Mesenchymal Transition - Lorena Avila-Carrasco; Pedro Majano; José Antonio Sánchez-Toméro; José Antonio Sánchez-Toméro; Rafael Selgas; Rafael Selgas; Manuel López-Cabrera; Manuel López-Cabrera; Abelardo Aguilera; Abelardo Aguilera; Guadalupe González Mateo; Guadalupe González Mateo; et al. (Frontiers Media S.A., 2019)
Epithelial-to-mesenchymal transition (EMT) is a self-regulated physiological process required for tissue repair that, in non-controled conditions may lead to fibrosis, angiogenesis, loss of normal organ function or cancer. Although several molecular pathways involved in EMT regulation have been described, this process does not have any specific treatment. This article introduces a systematic review of effective natural plant compounds and their extract that modulates the pathological EMT or its deleterious effects, through acting on different cellular signal transduction pathways both in vivo and in vitro. Thereby, cryptotanshinone, resveratrol, oxymatrine, ligustrazine, osthole, codonolactone, betanin, tannic acid, gentiopicroside, curcumin, genistein, paeoniflorin, gambogic acid and Cinnamomum cassia extracts inhibit EMT acting on transforming growth factor-β (TGF-β)/Smads signaling pathways. Gedunin, carnosol, celastrol, black rice anthocyanins, Duchesnea indica, cordycepin and Celastrus orbiculatus extract downregulate vimectin, fibronectin and N-cadherin. Sulforaphane, luteolin, celastrol, curcumin, arctigenin inhibit β-catenin signaling pathways. Salvianolic acid-A and plumbagin block oxidative stress, while honokiol, gallic acid, piperlongumine, brusatol and paeoniflorin inhibit EMT transcription factors such as SNAIL, TWIST and ZEB. Plectranthoic acid, resveratrol, genistein, baicalin, polyphyllin I, cairicoside E, luteolin, berberine, nimbolide, curcumin, withaferin-A, jatrophone, ginsenoside-Rb1, honokiol, parthenolide, phoyunnanin-E, epicatechin-3-gallate, gigantol, eupatolide, baicalin and baicalein and nitidine chloride inhibit EMT acting on other signaling pathways (SIRT1, p38 MAPK, NFAT1, SMAD, IL-6, STAT3, AQP5, notch 1, PI3K/Akt, Wnt/β-catenin, NF-κB, FAK/AKT, Hh). Despite the huge amount of preclinical data regarding EMT modulation by the natural compounds of plant, clinical translation is poor. Additionally, this review highlights some relevant examples of clinical trials using natural plant compounds to modulate EMT and its deleterious effects. Overall, this opens up new therapeutic alternatives in cancer, inflammatory and fibrosing diseases through the control of EMT process.